2019
DOI: 10.1021/acsaem.9b01428
|View full text |Cite
|
Sign up to set email alerts
|

A Depth-Profiling Study on the Solid Electrolyte Interface: Bis(fluorosulfuryl)imide Anion toward Improved K+ Storage

Abstract: Solid electrolyte interface (SEI) significantly affects alkaline metal ion battery performance in terms of reversible capacity, columbic efficiency and cycling stability.However, intrinsic properties of SEI layer in potassium ion batteries (KIBs), including structures, components, formation mechanism and corresponding K + storage behavior, are poorly understood. Here, we focus on the effect of electrolyte on SEI formation and K + storage behavior in self-supported nitrogen-doped graphite foams (NGFs).Two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…Electrolyte plays an important role on determining the K + storage properties of PIHCs. [ 28 ] In order to identify the appropriate electrolyte, NOCS‐60 was chosen as an example to investigate the representative K + storage behaviors of NOCSs anode in different electrolytes (0.8 m KPF 6 vs 1 m or 3 m KFSI in ethylene carbonate and diethyl carbonate (EC/DEC, 1:1 by volume ratio)). Compared to KPF 6 ‐based electrolyte, superior K + storage behaviors in terms of high Coulombic efficiency, good rate performance, and long cycling stability, are demonstrated in KFSI‐based electrolyte (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Electrolyte plays an important role on determining the K + storage properties of PIHCs. [ 28 ] In order to identify the appropriate electrolyte, NOCS‐60 was chosen as an example to investigate the representative K + storage behaviors of NOCSs anode in different electrolytes (0.8 m KPF 6 vs 1 m or 3 m KFSI in ethylene carbonate and diethyl carbonate (EC/DEC, 1:1 by volume ratio)). Compared to KPF 6 ‐based electrolyte, superior K + storage behaviors in terms of high Coulombic efficiency, good rate performance, and long cycling stability, are demonstrated in KFSI‐based electrolyte (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…After 50 cycles, the amount of ROCOOK increases for both KPF 6 (46 to 62 at.%) and KFSI (34 to 56 at.%) -based electrolytes, suggesting a relatively higher rate of accumulation of carbonate-based solvent degradation species. [9,24,25] At first sight, this might appear surprising in the light of the much lower CE for the KPF 6 -based electrolyte (Fig. 2) and the recent literature reporting the formation of thinner SEI with KFSI.…”
Section: Sei Passivation/ Stabilitymentioning
confidence: 87%
“…Recently, it was shown that the use of potassium bis(fluorosulfonyl)imide (KFSI) as the electrolyte salt produces a much more efficient SEI than that formed in the more conventional potassium hexafluorophosphate (KPF 6 ) salt. [9,24,25] In this work, we carefully investigate the electrochemical performance of self-supported CNF prepared by electrospinning as negative electrodes in KIB. As the performance is strongly influenced by the electrolyte, two different carbonate-based electrolytes were tested, using either KFSI or KPF 6 salts.…”
Section: Introductionmentioning
confidence: 99%
“…[75] Then the stabilization effect of KFSI on K metal, transitionmetal sulfide, alloybased, niobiumbased and carbo naceous anodes was further verified with the use of KFSIbased electrolytes, including Sn 4 P 3 , Bi, Sn, Sb, GeP 5 , red phosphorus, MoS 2 , NiCo 2.5 S 4 , K 4 Nb 6 O 17 , MoSe 2 /Ndoped carbon, graphite and nitrogendoped graphite foams. [39,[76][77][78][79][80][81][82][83][84][85][86][87] The enhanced Coulombic efficiencies and outstanding cycling performance mainly come from the formation of robust SEI layers, which suppress K dendrite growth and alleviate electrode volume changes during cycling.…”
Section: Organic Liquid Electrolytesmentioning
confidence: 99%
“…The intrinsic reasons for the difference between SEI layers formed in KFSI and KPF 6 electrolytes mainly lie in the difference of saltsolvent solvation behavior, as well as the LUMO energy levels of salts, solvents, and salt-solvent com plexes. [39,84,87] DFT calculation results reveal a higher K + ion solvation energy in KFSI electrolytes than that in KPF 6 electro lytes, which impedes the side reactions between K metal and free solvent molecules (Figure 11a). Moreover, DFT calculation results indicate that both KFSI and KFSI-solvent complexes have lower LUMO energies than KPF 6 and KPF 6 -solvent com plexes, respectively, implying a more reductive reactivity of KFSI species (Figure 4 and Figure 11b).…”
Section: Salt Dependency Of Sei Layermentioning
confidence: 99%